2015
DOI: 10.1016/j.surfcoat.2015.06.047
|View full text |Cite
|
Sign up to set email alerts
|

Electrochromics for energy efficient buildings: Towards long-term durability and materials rejuvenation

Abstract: Electrochromic devices such as "smart windows" for energy efficient windows must be durable enough for many years of practical use. Typical devices employ films based on W oxide and Ni oxide, and this paper surveys recent progress on durability-related issues for these materials. In the case of W oxide, we discuss the beneficial effects of Ti addition, and we describe recent and unexpected progress concerning galvanostatic rejuvenation of aged W oxide films. For Ni oxide, we report how charge exchange declinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Summarizing, we have used ToF-ERDA to demonstrate (i) that Li + intercalation can take place rather evenly throughout the cross-section of an electrochromic WO 3 -based film, which is different from the case of electrochromic NiO-based films where the interaction with Li + is a surface phenomenon; (ii) that the degradation of WO 3 -based films under excessive voltammetric cycling is associated with Li + trapping; and (iii) that galvanostatic rejuvenation of WO 3 films is unambiguously related to Li + detrapping. The results of this study are almost certainly applicable to other cathodically coloring electrochromic oxides, and possibly to batteries and other types of ionic-based devices.…”
mentioning
confidence: 74%
“…Summarizing, we have used ToF-ERDA to demonstrate (i) that Li + intercalation can take place rather evenly throughout the cross-section of an electrochromic WO 3 -based film, which is different from the case of electrochromic NiO-based films where the interaction with Li + is a surface phenomenon; (ii) that the degradation of WO 3 -based films under excessive voltammetric cycling is associated with Li + trapping; and (iii) that galvanostatic rejuvenation of WO 3 films is unambiguously related to Li + detrapping. The results of this study are almost certainly applicable to other cathodically coloring electrochromic oxides, and possibly to batteries and other types of ionic-based devices.…”
mentioning
confidence: 74%
“…C.G. Granqvist reviewed the gradual evolution of TCs and ECs in the latest years, highlighting the recent steps towards the commercial spread of such technologies: TC nanoparticles and VO 2 doping are reported as promising approaches for improving TC features; on the other hand, it was observed that mixed oxides will probably be a suitable strategy for future research outcomes; moreover, Wen et al [88] showed that degraded EC films, based on both W oxide and Ti oxide, can be rejuvenated by means of a suitable galvanostatic treatment. This important result may improve the cyclability of EC devices, extending the durability of smart windows.…”
Section: Considerations About Building-integration Of Chromogenic Tecmentioning
confidence: 99%
“…Spectral modulation of optical properties may result in an optimized tuning of the energy flux through glazing, with particular reference to the visible and infrared ranges of the impinging solar radiation. An accurate design and building integration of chromogenics may eventually reduce cooling/heating loads and enhance indoor visual comfort as well [153][154][155][156]. Over the last few decades, a strong impulse towards experimental research dealing with TiO 2 has come via nanoscience.…”
Section: Tio 2 In the Design Of Chromogenic Devices-general Considerationsmentioning
confidence: 99%